Uma aproximação às inovações no léxico político e social em Portugal na transição do século XVIII para o XIX : o caso do conceito de Revolução - de Brito, Ricardo (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
In the transition from the XVIIIth to the XIXth centuries, we witnessed developments (and innovations) in a significant part of the political and social lexicon in Europe. These new semantics gave meaning to political experience, which largely began with the French Revolution (1789). It is well known the revolutionary and counter-revolutionary cycle that originated from this “founding revolution” and lasted until the mid of the century. Central concept of this period, Revolution had a significant semantic evolution, which gave him new uses and meanings till then superficially explored. The aim of this paper is to trace the genealogy of these new conceptual paths of the concept in Portugal at the end of the Old Regime and the first decades of the nineteenth century